1981
DOI: 10.1115/1.3241741
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Cold and Reacting Flows Around a Bluff-Body Flame Stabilizer

Abstract: A confined oblique flame anchored on a bluff object was considered in a homogeneous propane/air mixture. A laser velocimeter employing a unique single-particle processor was used to quantify the turbulence velocity as well as spectrum. The results with combustion presented a striking contrast to the corresponding cold flow data. A major conclusion of the work is that the apparent suppression of turbulence observed in the separated combustion flow may be attributed to the significant dilatation effect by heat r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(18 citation statements)
references
References 0 publications
3
15
0
Order By: Relevance
“…That is, for flames with large density ratios across the flame, the BVK instability is suppressed [56,67,68]. For example, comparisons of velocity spectra show a narrowband peak in the non-reacting case that is absent in the presence of combustion, as shown in Fig.…”
Section: Exothermicity Influences On the Wake Flowmentioning
confidence: 89%
See 2 more Smart Citations
“…That is, for flames with large density ratios across the flame, the BVK instability is suppressed [56,67,68]. For example, comparisons of velocity spectra show a narrowband peak in the non-reacting case that is absent in the presence of combustion, as shown in Fig.…”
Section: Exothermicity Influences On the Wake Flowmentioning
confidence: 89%
“…For example, Fureby and Lofstrom point out that the vorticity field strength was much weaker and ''less structured'' [55] in the presence of combustion. Similarly, Fuji and Eguchi [56] and Bill and Tarabanis [57] noted that turbulence levels in the reacting flow were much lower than the non-reacting case, particularly in the vicinity of the recirculation zone boundary. This is apparently due to the stabilization of the BVK instability, as discussed in the next section, as well as the substantial increase in viscosity in the post-flame gases and the gas expansion induced vorticity sink.…”
Section: Exothermicity Influences On the Flow Fieldmentioning
confidence: 94%
See 1 more Smart Citation
“…Many researchers have studied the cold and reacting flows behind the bluff body using experiments or numerical simulations [5][6][7][8][9][10][11][12][13]. The unsteady, highly strained flow field in the wake of the bluff body contains large-scale coherent structures, which is a challenge to turbulence models.…”
Section: Introductionmentioning
confidence: 99%
“…The first experiments of Winterfeld [5] and Clare et al [6] have shown an increase of this length, while the ones of Grindley reported in [3], and Pitz and Daily [7] show the opposite. The studies of Taylor and Whitelaw [8], and Fuji and Egushi [9] show both an increase of the length.Indeed, it is easily understandable that combustion can have opposite influences: i) in the case of a confined duct, the combustion behind the bluff body leads to an increase of the gas specific volume, which, expectedly, produces a flow acceleration, but, less expectedly, compresses the recirculation zone upstream and decreases its length; ii) on the contrary, the dilatation of gases due to higher temperature within the recirculation zone itself can increase Turbulent Shear Flows 5 …”
mentioning
confidence: 99%